Математичне моделювання та дослідження властивостей повітропідігрівника котла - Галянчук, І. Р.; Кузнецова, М. Я. (Видавництво Львівської політехніки, 2014)
Запропоновано спеціальну структурну схему та відповідну математичну модель повітропідігрівника як системи взаємопов’язаних теплообмінників. Отримані результати можна використати як новий методичний апарат розрахунків повітропідігрівників, так і апарат для виявлення можливих удосконалень об’єкта. It is inefficient to use known methods of designing and verification in solving operational problems when determining the influence of various operational changes on the performance of a boiler for air heating, since it is necessary to have a considerable amount of information that is difficult to obtain in operating conditions. In this paper we propose a block diagram and the corresponding mathematical model of an air heating boiler as a system of interconnected heater exchangers which utilizes only data about incoming and outgoing water temperature in the initial mode. On the basis of operating mode calculations a mathematical model of the heat exchange system, based on a two-way heat exchanger was developed. Application of the developed mathematical models allows for regime calculations of boilers' heating surfaces knowing only operational parameters (such as coolant temperature in one of the modes of the equipment operation) and objective parameters (coolant flow rate, area and condition of heating surfaces) may remain unknown.
Keywords: повітропідігрівник; математична модель; теплоносій; параметри; система; air heating boiler; mathematical model; coolant; parameter; system